Development of a compact near-infrared lamp furnace for synchrotron powder diffraction and its application for in situ high-temperature observation of ferrite magnets - Shintaro Kobayashi; Shogo Kawaguchi (Science and Technology of Advanced Materials: Methods)
The effective development of functional materials requires a thorough understanding of their high-temperature thermodynamic properties under material production process conditions. In this study, we develop high-temperature synchrotron X-ray diffraction (XRD) techniques using a compact near-infrared (NIR) lamp furnace at BL02B2 and BL13XU in SPring-8, enabling heating to ~ 1700 °C at a maximum rate of 1000 °C/min. The compactness of the device allows easy installation within the limited space around a goniometer in the beamline and facilitates simple sample exchange and positioning. The NIR furnace supports various measurement types using two different setups. One setup involves sample holders with flat sapphire sample cells, enabling measurements under various gas atmospheres and precise temperature control through direct temperature measurements near sample positions using a thermocouple. The other involves a capillary rotation system, allowing for sufficient particle statistical measurements even as crystal grain growth progresses. To demonstrate the applicability of the developed system for in situ experiments under various heating conditions, we evaluated the heating process of standard samples and in situ crystalline phase changes of Sr ferrite permanent magnet materials. Specifically, we successfully observed the calcination synthesis of the permanent magnet material, M-type SrFe12O19, from a mixture of SrCO3 and Fe2O3. Moreover, in situ heating observations were utilized to establish a pseudo-binary diagram of the SrFe12O19-Fe2O3 system above 1300 °C, including multiple Sr ferrite magnet phases (M-type SrFe12O19, X-type Sr2Fe30O46, and W-type SrFe18O27). Harnessing NIR lamp furnace adaptability facilitated in situ XRD observations for visualizing diverse high-temperature treatment procedures for functional materials.